Regulations governing the internal rules of worker cooperatives and determining working conditions - Escribano Gutiérrez, Juan (REVESCO. Revista de Estudios Cooperativos, 2022)
Despite their scant regulatory and doctrinal treatment, the Internal Regulations have enormous potential for regulating working conditions in worker co-operatives. An exhaustive examination of the doctrinal studies that have appeared to date shows that they lack detailed treatment beyond the odd classic study from a commercial perspective. On the contrary, there are no precedents for this type of study about the analysis of their role in the regulation of the working conditions of worker-members. The constitutive exclusion, from the 1990s onwards, of these members from the scope of application of labour law prevents the application of the instruments of collective regulation of the working conditions of employees, so that these regulations are the only vehicle for the collective regulation of their working conditions. An analysis of the various cooperative rules reveals, moreover, the dispersion and heterogeneity of the provisions governing these self-regulation instruments. For their part, the nature of these internal rules differs from the traditional instruments of collective regulation provided for by labour law. An analysis of their legal nature and limits is therefore necessary. Finally, some internal regulations of large cooperatives will be analysed to check whether and in what sense they are effectively taking on the regulation of such conditions. Specifically, the RRIs of the co-operatives Servicarne and Eroski will be analysed. In the first case, because of the jurisprudential controversy surrounding it and to be able to check whether this is reflected in their Internal Regulations. In the second case, to see how these Internal Regulations sometimes serve to exclude the application of important labour law institutions within the worker cooperative.
Keywords: Collective bargaining; Assembly; Internal democracy; Self-regulation